2016
DOI: 10.1080/10503307.2016.1197439
|View full text |Cite
|
Sign up to set email alerts
|

Therapist interventions and client ambivalence in two cases of narrative therapy for depression

Abstract: This supports the theoretical explanation that the therapist did not match client's developmental level in the poor-outcome case, working beyond the client's current TZPD and contributing to the maintenance of ambivalence.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
10
0
5

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 20 publications
(18 citation statements)
references
References 38 publications
(50 reference statements)
1
10
0
5
Order By: Relevance
“…Although the clients might have wished to decrease their experience of suffering and might have wanted to change with the help of the therapist, it is possible that they were blocked in the process of collaboration if they were anticipating change as having undesirable implications in their self-meanings or narrative structure. This would be consistent with studies that focused on impasses and blocks of change (Feixas et al, 2013;Ferreira et al, 2015;Gabalda & Stiles, 2009;Ribeiro et al, 2014Ribeiro et al, , 2016aRibeiro et al, , 2016bStiles, Gabalda, & Ribeiro, 2016), which suggest that self-conflicts regarding the experience of change may be involved in an increasing non-collaborative interaction and, subsequently, in dropout cases of therapy.…”
Section: Discussionsupporting
confidence: 86%
See 1 more Smart Citation
“…Although the clients might have wished to decrease their experience of suffering and might have wanted to change with the help of the therapist, it is possible that they were blocked in the process of collaboration if they were anticipating change as having undesirable implications in their self-meanings or narrative structure. This would be consistent with studies that focused on impasses and blocks of change (Feixas et al, 2013;Ferreira et al, 2015;Gabalda & Stiles, 2009;Ribeiro et al, 2014Ribeiro et al, , 2016aRibeiro et al, , 2016bStiles, Gabalda, & Ribeiro, 2016), which suggest that self-conflicts regarding the experience of change may be involved in an increasing non-collaborative interaction and, subsequently, in dropout cases of therapy.…”
Section: Discussionsupporting
confidence: 86%
“…Considering all the cases that the therapist was responsible for, including the cases selected for this study, the therapist attended a total of 34 cases of narrative therapy, from which 26.47% were successful completers, 38.26% were unsuccessful completers, 5.88% were successful dropouts, and 29.41% were unsuccessful dropouts. Despite the different outcomes, previous case studies using the TCCS (e.g., Ferreira, Pinto, Ribeiro, Pereira, & Pinheiro, 2015;Ribeiro et al, 2014Ribeiro et al, , 2016a consistently demonstrate that this therapist tended to intervene according to challenging strategies since the beginning of the therapy.…”
Section: Methods Participantsmentioning
confidence: 85%
“…A series of intensive case studies of assimilation progress in different therapeutic models has shown that good outcome clients, as assessed by standard symptom intensity measures, progress toward high APES levels across their sessions (e.g., Brinegar, Salvi, & Stiles, 2008;Caro Gabalda, 2011;Caro Gabalda, Stiles, & Pérez Ruiz, 2016;Gray & Stiles, 2011;Honos-Webb, Stiles, & Greenberg, 2003;Knobloch, Endres, Stiles, & Silberschatz, 2001;Mendes et al, 2016;Osatuke et al, 2007;Ribeiro, Braga et al, 2016a;Ribeiro, Cunha et al, 2016b). For example, in a study of one good outcome client, Basto et al (2016) found a strong negative correlation across 16 sessions of CBT between APES level and symptom intensity.…”
Section: Relation Of Assimilation To Therapy Outcomementioning
confidence: 99%
“…Despite the difference in conceptualizations, both empathy and challenge are observable in the actual interaction across different psychotherapy approaches ( Bänninger-Huber and Widmer, 1999 ; Voutilainen et al, 2010 ; Ribeiro et al, 2013 ; Weiste and Peräkylä, 2014 ) and both have positive association with therapeutic outcome ( Orlinsky and Howard, 1986 ; Keijsers et al, 2000 ; Elliot et al, 2011 ). Although empathy and challenge can be seen as diverging orientations, in reality they often co-exist ( Bänninger-Huber and Widmer, 1999 ; Voutilainen et al, 2010 ; Ribeiro et al, 2016 ).…”
Section: Introductionmentioning
confidence: 99%